Formas para el silencio - Río Diéguez, María del (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2006)
The creative act is necessary and healthy, because it puts us in touch with life, with our own biography, our own body and allows to integrate the experience of living us, to show what we are. Artistic creation, when it is understood as therapeutic route, does not mean production of beautiful forms, but transformation of the real world across fusing and to mix experiences, emotions, desires, recollections, with forms and matters (objects, colors, textures, images), making possible that experience of silence, before the limitation of language, gives name to what we feel, and in a healthy way. From this point of view, artists and patients can share a common plot.